Exercise 1 in section 7.1 of Dummit and Foote: Abstract Algebra is as follows:

================================================== ====

Let R be a ring with 1

Show that $\displaystyle {(-1)}^2 = 1$

================================================== =====

The web site Project Crazy Project gives the following proof:

================================================== ====

Let $\displaystyle x \in R$

Then $\displaystyle {(-1)}^2 x = (-1)(-x) = x$

Similarly $\displaystyle x {(-1)}^2 = (-x)(-1) = x$

By the uniqueness of 1, $\displaystyle {(-1)}^2 = 1$

================================================== ===

I am not sure why $\displaystyle {(-1)}^2 x = (-1)(-x)$

I can see that by associativity of multiplication $\displaystyle {(-1)}^2 x = (-1)[(-1)(x)]$

But then why is (-1)x = -x ... or is this just a formal way of expressing the same thing?

Further why is (-1)(-x) = x?

Peter